Trusses of tensegrity type in a concept of train station renovation in Żary = Koncepcja renowacji żarskiego dworca z wykorzystaniem kratownic typu tensegrity - Lechocka, Paulina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The first railway station in Żary was built in 1843 in Germany. After the Second World War and years of socialism in Poland the meaning of railway decreased and its technical condition deteriorated. Now the building needs renovation and change of function. Tensegrity structures may be useful in renovation of platforms shelter.
Keywords: tensegrity; kratownice; dworzec kolejowy; Żary; railway station